(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study examines the genderological features of male and female speech across languages of different structures, analyzing linguistic, sociolinguistic, and cultural factors that shape gendered communication. Phonetic, lexical, grammatical, and pragmatic distinctions between male and female speech are explored in Uzbek, Russian, English, Japanese, Akan, Djirbal, and several other languages. The study further highlights the influence of social, religious, and cultural contexts on the formation of gender-specific speech norms.